(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
India’s regional history has been reflected in its language, architecture, sculpture, painting, customs, and above all its folk culture. Bhupatinagar is a remote village in East Medinipur district on the southwest border of West Bengal. Geographically, this part of East Medinipur is close to Orissa, as a result, the region is related to Orissa in terms of language and culture. Art culture, religious thought, rituals, and folk cultures of this region are composed based on geography, climate, social structure, group tradition, people meeting, etc. The main beauty of this region is that numerous terracotta temples are situated in different places in Bhupatinagar with their class and full of verities. Based on history, archaeology, and folklore terracotta temple of this region has plentiful significance and importance. These temples were not only built for the performance of religious duties but also a significant example of the cultivation of art. Specifically, terracotta plaques fixed on temples comprise valuable elements for reconstructing the mythological and socio-cultural heritage. The themes of the terracotta plaques are mainly based on the stories of Ramayana, Mahabharata, and mythologies. At present, most of the temple’s conditions are in the worst situation. Some of the famous temples are being conserved, but most of the temples are in a ruined situation. Properly and scientifically these temples must be conserved to retain the heritage of this region. Minimum written documents have been published on this subject. Mostly it has been studied description rather than an analysis of these temples. Another significant culture of this region is the worship of mundane deities. Various legends and temples have been created around these worldly deities. People not only respect but also believe in these folk culture and religious ideas that have been passed down for a long time, even before the worship of mythological gods and goddesses. Due to the spread of worship, people of high caste also offered their worship at the feet of those gods and goddesses out of fear or devotion. The hymns were written in Sanskrit. The terrestrial deities have their place in the same temple besides the mythological deities. This can be called the Aryanization of folk gods and goddesses. Mainly worshiped as village deities, most of those deities are also prevalent in other districts of Bengal, such as Mansa, Sheetala, Sarvamangala, Vishalakshi, and Chandi. Some deities are worshiped only in these areas of Medinipur district, such as Govinda Roy, Kalurai, Shankeshwari, and Mugeshwari. In this article, our main focus to discuss is the regional antiquities (religious culture, architecture,) of Bhupatinagar and the reconstruction of temple-centric folk culture.